Cycle Stability of Dual-Phase Lithium Titanate (LTO)/TiO2 Nanowires as Lithium Battery Anode - Yillin Fan He; Dongzhi Yang Chu; Zhensheng Zhuo (Journal of Multidisciplinary Applied Natural Science, 2021)
This work studied cycle stability of dual-phase lithium titanate (LTO)/TiO2 nanowires as a lithium battery anode. Dual-phase LTO/TiO2 nanowires were successfully synthesized by hydrothermal method at various times lithiation of 10, 24, and 48 h at 80 °C. SEM images show that the morphology of dual-phase LTO/TiO2 is nanowires with a size around 100-200 nm in diameter. The XRD analysis result indicates nanowires main components are anatase (TiO2) and spinel Li4Ti5O12. The first discharge specific capacity of LTO/TiO2-10, LTO/TiO2-24, and LTO/TiO2-48 was 181.68, 175.29, and 154.30 mAh/g, respectively. After the rate capacity testing, the LTO/TiO2-10, LTO/TiO2-24, and LTO/TiO2-48 have been maintained at 161.25, 165.25, and 152.53 mAh/g separately. The retentions for each sample were 86.71, 92.86, and 89.79 %. Based on the results of electrochemical performance, increased LTO content helped increase samples cycle stability. However, the prolonged lithiation time also produced impurities, which reduced the cycle stability.